Improving parenting practices and development for young children in Rwanda: Results from a randomized control trial. (May 2020) - Abimpaye, Monique; Dusabe, Caroline; Nzabonimpa, Jean Providence; Ashford, Richard; Pisani, Lauren
It is well known that the first 1, 000 days of life have long-lasting impact on a child's cognitive, language, socio-emotional, and physical development, but there is little evidence from Rwanda about how to maximize parent–child interactions during these critical early years. Save the Children piloted the First Steps "Intera za Mbere" early childhood parenting education program in one district of Rwanda to promote healthy development through holistic parenting education. Using a cluster randomized control trial, we assessed outcomes of a 17-week parenting education on parenting skills and child development for families with children aged 6–36 months. Families were randomly allocated into three study groups: light touch ( n = 482), full intervention ( n = 482), and control ( n = 483) groups. We used a Kinyarwanda-adaptation of the validated Ages & Stages Questionnaires (ASQ), a Home Observation Measurement of the Environment-Short Form. Multivariate linear and logistic regression analyses were used for both the intention-to-treat analyses and more robust models controlling for ASQ form received, child gender, maternal education, number of children in the home, and baseline ASQ scores. Findings indicate that children in the light touch and full intervention groups were significantly more likely to meet the ASQ benchmarks than the control group in all developmental domains. The strong positive results from the light touch group are especially relevant to efforts to bring beneficial early childhood stimulation programs to scale in low-income contexts.